Modulation of fatty acid metabolism and immune suppression are features of in vitro tumour sphere formation in ontogenetically distinct dog cancers. (20th November 2017) - Kim, J.‐H.; Frantz, A. M.; Sarver, A. L.; Gorden Klukas, B. H.; Lewellen, M.; O'Brien, T. D.; Dickerson, E. B.; Modiano, J. F.
Abstract : Non‐adherent, 3‐dimensional sphere formation is used as an in vitro surrogate to evaluate cellular potential for tumour initiation and self‐renewal. To determine if a shared molecular program underlies the capacity for sphere formation by cells originating from diverse tumour types, we characterized molecular and functional properties of 10 independent cell lines derived from 3 ontogenetically distinct dog cancers: hemangiosarcoma, osteosarcoma and glial brain tumours. Genome‐wide gene expression profiling identified tumour‐of‐origin‐dependent patterns of adjustment to sphere formation in a uniform culture condition. However, expression of the stem/progenitor markers CD34 and CD117, resistance to cytotoxic drugs and dye efflux (side population assays) showed no association with these gene expression profiles. Instead, primary sphere‐forming capacity was inversely correlated with the ability to reform secondary spheres, regardless of tumour ontogeny. Primary sphere formation seemed to be proportional to the number of pre‐existing cells with sphere‐forming capacity in the cell lines. Cell lines where secondary sphere formation was more proficient than primary sphere formation showed enrichment of genes involved in fatty acid synthesis and immunosuppressive cytokines. In contrast, cell lines where secondary sphere formation was approximately equivalent to or less proficient than primary sphere formation showed upregulation of CD40 and enrichment of genes involved in fatty acid oxidation. Our data suggest that in vitro sphere formation is associated with upregulation of gene clusters involved in metabolic and immunosuppressive functions, which might be necessary for self‐renewal and for tumour initiation and/or tumour propagation in vivo.